Galskab og hellighed: Overskridelsens logik og retorik i chan/zen-buddhismen - Borup, Jørn (Religionsvidenskabeligt tidsskrift, 2019)
Antinomian transgressions have played an important role in Chinese Chan Buddhism (and to a lesser extent in Japanese Zen Buddhism). Wild, crazy, fierce and strange figures have, together with 'the enlightened layman', been used as expressions of the Chan/Zen universe, whose style is quite unique in the history of religions. The present article investigates these transgressions' hermeneutic and performative logic as a contrast to the 'religion of order' which is also represented by Buddhism. I argue that in both phenomenological and historical perspective these are expressions of post-axial religion.